Effects of high-fat diet on insulin receptor function in rat hippocampus and the level of neuronal corticosterone - Pratchayasakul W. (2014)
Aim: Chronic consumption of a high-fat (HF) diet contributes to peripheral insulin resistance and elevated plasma corticosterone. However, the effect of HF consumption on the neurofunctional insulin receptors and neuronal corticosterone level is unclear. We tested the hypothesis that HF consumption can lead to peripheral insulin resistance, elevated neuronal corticosterone, and impaired neuronal responses to insulin. Main methods: Male Wistar rats were fed with normal diet or HF diet for 4, 8 or 12 weeks. At the end of each dietary period, plasma was collected for investigating peripheral insulin resistance parameters and corticosterone. Brains were then rapidly removed for studying the function of neuronal insulin receptors (IRs) by extracellular recording in CA1 hippocampus, neuronal IR signaling by immunoblot technique and neuronal corticosterone. Key findings: Elevated plasma corticosterone level was initially seen in 4-week HF-fed rats. Peripheral insulin resistance developed at 8-week HF-fed rats. However, the elevated neuronal corticosterone level was found at 12-week HF consumption. The neuronal IR response demonstrated by insulin-mediated long-term depression in CA1 hippocampus was diminished in 12-week HF-fed rats. The phosphorylation levels of neuronal IR, IR substrate 1 and Akt/PKB were decreased in 12-week HF-fed rats with no change in these proteins. There was a correlation among peripheral insulin resistance, neuronal stress (elevated neuronal corticosterone), and neuronal insulin resistance in HF group. Significance: Our findings suggest that HF consumption can lead to the elevation of corticosterone and peripheral insulin resistance, which could contribute to neuronal insulin resistance and neuronal stress. © 2011 Elsevier Inc.